Peculiarities of domain walls with vertical Bloch lines at low temperatures - Dovgij, V. T.; Kalkin, A. A.; Astaf`eva, T. G.; Bar`yakhtar, F. G.; Yampolskaya, G. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The results of experimental studies of the vertical Bloch line (VBL) generation and stability in the epitaxial iron-garnet films (EIGF) with different compounds, anisotropy, implantation, and compensation temperatures are presented. It is shown that the critical fields of the VBL generation and annihilation in the stripe domain (SD) walls increase and that its values differ considerably (the VBL stability region increases) with decreasing temperature. The domain period increases as a result of magnetic inhomogeneities of the domain walls. The magnetic profile and the energy potential barrier account for the existence of the metastable domain structures with different periods. It is established that the VBL existence domains are limited by the region near the Neel temperature TN and the compensation point temperature Tc (in films with Tc).